Mengoptimalkan Kesadaran Remaja tentang Bahaya dan Akibat Penyalahgunaan Narkoba: Inisiatif Pelibatan Masyarakat di SMA Bina Insan Mandiri Depok (Neolectura, 2023)
This study revolves around heightening adolescent awareness concerning the perils and consequences linked to drug misuse, accomplished via a community engagement initiative at SMA Bina Insan Mandiri Depok. The concerted endeavor involving the implementation team from Sekolah Tinggi Ilmu Hukum IBLAM (STIH IBLAM) and the institution itself yielded a range of insightful activities, encompassing systematic material delivery, interactive gaming, knowledge appraisal, and awareness advocacy. Subsequent evaluation showcased a substantial escalation in students' grasp of drug-related matters after the intervention. This strategic partnership between educational entities and the community emerges as a pivotal approach in grappling with the escalating concern of drug abuse among the youth.